Characterization of extracellular electron transfer networks in Geobacter sulfurreducens, a key bacterium for bioremediation and bioenergy applications - Dantas, Joana Margarida Franco (2018)
Geobacter bacteria have awakened significantly attention because of their impact on natural environments and biotechnological applications that include the bioremediation of organic and inorganic contaminants, bioenergy production and bioelectronics. In addition to electron transfer towards extracellular terminal acceptors, Geobacter cells can also accept electrons from electrodes, in currentconsuming biofilms, a process that is currently explored in microbial electrosynthesis. These practical applications rely on an efficient transfer of electrons between the cell and its exterior, a process designated extracellular electron transfer (EET). However, the precise mechanisms underlying EET processes are still under debate. Genetic and proteomics studies have identified several c-type cytochromes as key components for EET in G. sulfurreducens. These proteins are located at the innermembrane (IM), periplasm and outer-membrane (OM). Examples of such cytochromes include the IMassociated cytochrome MacA, periplasmic cytochromes PpcA-E and PccH, as well as, the OM cytochrome OmcF, which were studied in this Thesis. Molecular interactions between PpcA-E and their putative redox partners, including a humic substance analogue molecule, MacA or PccH, were probed by NMR spectroscopy, stopped-flow kinetics and molecular docking. For the interacting pairs, their binding affinity was also determined by NMR chemical shift perturbation experiments. The results obtained showed that the interacting molecules establish reversible low-binding affinity complexes in specific regions of the proteins to warrant a rapid and selective electron transfer, a typical feature observed for electron transfer reactions between redox partners. In addition, NMR spectroscopy was also used to determine the solution structure of OmcF in the reduced state, its pH-dependent conformational changes and backbone dynamics. A biochemical and structural characterization of the cytochrome PccH was also carried out using circular dichroism, UV-visible and NMR spectroscopic techniques. The structure of PccH determined by X-ray crystallography showed that it is unique among the monoheme c-type cytochromes. The reduction potentials determined for PccH at different pH values by visible redox titrations are unusually low compared to those reported for other monoheme c-type cytochromes. Considering the structural and functional features of PccH it was proposed that this protein represents a first characterized example of a new subclass of monoheme c-type cytochromes. Overall, the results obtained constitute an important contribute to the current understanding of the G. sulfurreducens extracellular electron transfer mechanisms.